Molecular Phylogenetic Analyses of Two Ray-Finned Fishes Acanthurus mata (Cuvier, 1829) and Ephippus orbis (Bloch, 1787) From the Odisha Coast, Bay of Bengal, India - BIJAYALAXMI SAHU; TAPAN KUMAR BARIK; AMIYA KUMAR PATEL (Asian Fisheries Science)
Two fish species Acanthurus mata and Ephippus orbis of the order Acanthuriformes were collected from Gopalpur-onsea, Bay of Bengal, where they were recorded for the first time. Both the fishes were identified using the conventional taxonomic methods followed by the molecular taxonomic method of DNA barcoding using the mitochondrial cytochrome c oxidase subunit I (COI) gene. All COI barcodes produced in this investigation were matched with reference sequences of anticipated species by morphological identification. Based on DNA barcodes, neighbour-joining, and maximum likelihood phylogenetic trees were constructed, and all of the specimens found were clustered according to their species-level taxonomic categorisation. To derive haplotype diversity, a median-joining network was built. The current study additionally looked at the number of variable sites, parsimony informative sites, nucleotide diversity, and variation in amino acids. Significant genetic variations were detected among A. mata species from various geographic regions. However, E. orbis still has highly conserved natural populations with no significant variations. The findings of this work provide information on the phylogeny, population dynamics, divergence time, and genetic diversity of both fish species as well as substantial validation for the use of DNA barcode sequences for tracking species diversity.